1993
DOI: 10.1002/sia.740200905
|View full text |Cite
|
Sign up to set email alerts
|

Ion scattering and electron spectroscopic study of the surface coverage of V/Al2O3 catalysts

Abstract: Ion scattering spectroscopy (ISS) and x-ray photoelectron spectroscopy (XPS, ESCA) were used to study the dispersion of the vanadium phase and the coverage of Al,O, by vanadium. A series of V/AI,O, catalysts was prepared by equilibrium adsorption with vanadium loadings varying from 1.9 to 6.7 wt.% V. By monitoring the ISS AI/O intensity ratio the surface coverage of the catalysts was determined. The surface coverage increases from 15 to 33% with increasing the loading from 1.9 to 3.5 wt.% V. The results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…This is a remarkable result despite the fact that the surface Mo density of this catalyst is somewhat above the monolayer limit, because it has been claimed sometimes in the literature that the support (ZrO 2 , TiO 2 , Al 2 O 3 ) remains exposed at transition metal oxide (W, Mo, V) loadings above monolayer surface coverage. 16 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is a remarkable result despite the fact that the surface Mo density of this catalyst is somewhat above the monolayer limit, because it has been claimed sometimes in the literature that the support (ZrO 2 , TiO 2 , Al 2 O 3 ) remains exposed at transition metal oxide (W, Mo, V) loadings above monolayer surface coverage. 16 …”
Section: Discussionmentioning
confidence: 97%
“…On the basis of such measurements it has been argued that the support is only covered to ¾85% (55%) in WO 3 /TiO 2 WO 3 /ZrO 2 catalysts with tungsten contents above the theoretical monolayer surface coverage. 18,21 Formation of transition-metal oxide multilayers at incomplete coverage of the oxide support has been claimed also for V 2 O 5 /Al 2 O 3 catalysts, 16 and in early studies of alumina-supported Mo and W oxides the support line was still detected at transition-metal oxide contents far above the theoretical monolayer surface coverage. 10,15 The history of the samples studied is not always clear in the literature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…X-ray photoelectron spectroscopy (XPS) provides information about the oxidation state and the chemical environment of a given atom due to shifts in the binding energies [97][98][99][100][101][102][103][104][105]. The structural information is, however, limited since XPS cannot discriminate between different VO x structures possessing the same oxidation state, i.e.…”
Section: Bm Weckhuysen De Keller / Catalysis Today 78 (2003) 25-46mentioning
confidence: 99%
“…21,22 The selection of the ISS method is based on recent results from our laboratory, which showed that the technique, because of its sensitivity to the top atomic layer of the surface, can be used e †ectively to determine the surface coverage of monolayer-like catalysts. 23 The purpose of the present work is to evaluate the potential use of the chemisorption method for the CO 2 determination of the surface coverage of cataMo/TiO 2 lysts. The surface coverage of the titania support by Mo was monitored by chemisorption and the results CO 2 were compared with those obtained by ISS.…”
Section: Introductionmentioning
confidence: 99%